Optimization of Cathode Catalyst Layer of PEFC Using Silk-Derived Activated Carbon by 2-Step Mixing Method. (10th January 2017) - Fukunaga, Hiroshi; Anto, Naofumi; Kushibiki, Kanshi; Shimada, Iori; Osada, Mitsumasa; Takahashi, Nobuhide
Abstract : Effect of organic solvent used in the catalyst ink was investigated using Silk activated carbon (SAC) as metal-free PEFC cathode catalyst. A novel preparation method by mixing the ink by two steps, i.e., mixing catalyst and ionomer with 1-Propanol (NP) in the first step and then mixing carbon black and Butyl acetate (BA) in the second step, was developed. MEA prepared by using BA and NP in the catalyst ink showed different tendency at low and high current density, indicating different microstructure of the catalyst layer due to the different ionomer formation. Two step mixing increased the performance, suggesting the coverage of ionomer by solution formation, and the increased continuity of ionomer by colloid formation. The optimum mixing ratio of SAC and ionomer was 1:1. NP used in the first step was effective at low current density, whereas BA used in the second step was effective at high current density.